Trauma-Informed Risk Assessment in Correctional Settings - K. Bates-Maves, Julie; O’Sullivan, Deirdre (International Journal of Criminology and Sociology, 2017)
This paper outlines a model which infuses trauma-informed principles into the existing Risk-Needs-Responsivity model of risk assessment commonly used in correctional settings. The connection between certain types of trauma and criminality is established. Despite this, many risk assessment procedures do not include screening for trauma, or trauma-specific interventions. An overview of the lasting effects of childhood maltreatment is included. Trauma-informed practices and assessment recommendations are also provided, along with recommendations for additional resources